Selection of Packaging Supplier Manufacturing Industry PT. ABC in East Java with An Analytical Hierarcy Process (AHP) Approach - Nicholaus Gede Rio G. M (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research was conducted to study and analyze problems related to supplier selection in manufacturing companies. Data collection was carried out by means of interviews, observation and literature study. Data processing uses the AHP approach. The results of data processing using the AHP method can be obtained from several alternative suppliers, namely "GA", "BS", "PO", while the criteria include quality, price and service. Then, using AHP, the results of Suppliers that are recommended to be prioritized by taking into account the three criteria are found in the first order, namely Supplier GA with a priority weight of (0.657), then the second priority order is Supplier BS with a weight of (0.237) and the third priority is Supplier PO with a weight of (0.104).